2006
DOI: 10.1074/jbc.m606723200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Interactions of Kleisins and DNA with Bacterial Condensin MukB

Abstract: MukBEF is a bacterial SMC (structural maintenance of chromosome) complex required for faithful chromosome segregation in Escherichia coli. The SMC subunit of the complex, MukB, promotes DNA condensation in vitro and in vivo; however, all three subunits are required for the function of MukBEF. We report here that MukEF disrupts MukB⅐DNA complex. Preassembled MukBEF was inert in DNA binding or reshaping. Similarly, the association of MukEF with DNA-bound MukB served to displace MukB from DNA. When purified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
117
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(128 citation statements)
references
References 41 publications
(100 reference statements)
11
117
0
Order By: Relevance
“…These two amino acid substitutions are the equivalent of the R216E and R218E mutations made in Haemophilus ducreyi MukB that elicited DNA binding deficiency (13). These two mutations sit on the head domain of the MukB dimer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two amino acid substitutions are the equivalent of the R216E and R218E mutations made in Haemophilus ducreyi MukB that elicited DNA binding deficiency (13). These two mutations sit on the head domain of the MukB dimer.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the head domains in a MukB dimer are also non-equivalent. (27), (ii) that the pre-formed MukBEF complex is defective in binding plasmid DNA (13), and (iii) that adding MukEF to a MukB-DNA complex appears to displace MukB from the DNA (13). Our observations are consistent with these previous observations; however, we observe distinct inhibition of the MukB-mediated catenation reaction by the addition of ATP, with less inhibition observed with AMP-PNP, and no inhibition observed with ADP.…”
Section: Topological Alteration Of the Dna Observed In The Reactions mentioning
confidence: 99%
See 1 more Smart Citation
“…Because full-length MukB affects the supercoiling and condensation of DNA (20,21,23,24), we also probed the ability of MukB-D, which lacks the DNA-binding head domain and much of the coiled coil (44) to stimulate Topo IV function. As with intact MukB, we observe that MukB-D is sufficient to stimulate the DNA decatenation and relaxation activities of Topo IV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both E. coli mukB − strains and smc − strains from Bacillus subtilis and Caulobacter crescentus show temperature-sensitive colony formation and an increase in the number of anucleate cells at the permissive temperature, suggesting a deficiency in chromosome segregation (5,7,(15)(16)(17)(18)(19). Moreover, a convincing array of experiments has demonstrated that MukB functions as a condensin in vitro and in vivo (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%